Change in waist circumference over 3 years in Turkish children and adolescents. (September 2013) - Unalan, Demet; Senol, Vesile; Bayat, Meral; Mazicioglu, Mustafa Mumtaz; Ozturk, Ahmet; Kurtoglu, Selim; Hatipoglu, Nihal; Ustunbas, Hasan Basri
Abstract Aim: To observe change in waist circumference (WC) over 3 years in children and adolescents and to compare these data with local and international references. Subjects and methods: The data of the second study determining the anthropometric measurements of Turkish children and adolescents (DAMTCA-II) were used to calculate WC percentiles. A total of 4234 children and adolescents aged 6–17 years (1890 boys and 2344 girls) were enrolled. The 3rd, 5th, 10th, 25th, 50th, 75th, 85th, 90th, 95th and 97th percentiles and z-scores were computed by the LMS Method. Results: The mean WC was significantly higher in boys than in girls in 12.5, 13 and 15–17 year old children (p < 0.001). The prevalence of central obesity (WC ≥ 90th percentile) was 13.5% (14.3% in boys and 12.9% in girls, respectively). There was no significant difference in prevalence of abdominal obesity, between each gender (p = 0.179) and age group from 6–17 years (p = 0.590). In a comparison with the available contemporary international references, the 50th percentiles of these references were similar to those in Bulgaria, but markedly higher than those of Malaysian children and of Chinese children living in Hong Kong. Conclusions: The prominent finding of this study was the significant increase in WC percentiles in a short time in both genders. In addition, the WC references are similar to other regional references, but significantly higher than those of East Asia.